Proving the Siddikin Argument in the Quran from the point of view of Ayatollah Javadi Amoli - ahmad maleky; ahmad maleky (حکمت اسرا)
Siddiqui's argument is proof of the existence of God without the mediation of creatures. Al-Farabi proposed this method and Ibn Sina claimed to have established this argument by presenting the proof of "possibility and obligation", which was objected to by Mullah Sadra, and finally, Mullah Sadra himself and after him, Allameh Tabataba'i, each presented a new version. They presented this proof. Hazrat Ayatollah Javadi Amoli, on the one hand, in argumentative debates, has disputed with the same criteria that Mulla Sadra disputed in Ibn Sina's argument of being a Siddiqui, in Mulla Sadra's argument itself, and finally emphasizes the argument of Allameh Tabataba'i, and on the other hand, in arguments Tafsir has discussed the Qur'anic evidence on this argument. This research, with descriptive and analytical method, aims to answer this question: How is the explanation of Siddikin's argument and its Quranic evidence from the perspective of Ayatollah Javadi Amoli? As a response, after the presentation of Siddikin's argument from the point of view of Ayatollah Javadi Amoli, he has endeavored to explain its Quranic evidence with regard to verse 45 of Surah Furqan and 53 of Surah Al-Fazlat and to explain the testimony and implications of each of the verses on the claim, so that Firstly, it is an example of the rationality of the concepts of the Quran, secondly, it is a manifestation of the inseparability of the Quran and proof in an objective and exemplary manner, and thirdly, it shows an aspect of the scientific miracle of this divine book.